Functional characteristics and sites of gene expression of the alpha 1, beta 1, gamma 2-isoform of the rat GABAA receptor - Malherbe, P (J Neurosci, 1990)
GABAA receptors, the major synaptic targets for the neurotransmitter GABA, constitute gated chloride channels. By their allosteric, drug- induced modulation, they serve as control elements for the regulation of anxiety, vigilance, and epileptiform activity. The structural requirements of fully functional GABAA receptors in the mammalian brain have remained elusive so far. We report here on the cloning of the gamma 2-subunit cDNA of rat brain and its functional analysis by coexpression with the alpha 1- and beta 1-subunits in Xenopus oocytes, and on the sites of gene expression of the 3 subunits in the rat brain. The recombinant receptor displayed GABA-inducible currents (Imax = 6 microA; Ka = 75 microM) which were allosterically modulated by benzodiazepine receptor ligands (enhancement and inhibition by diazepam and methyl-6,7-dimethoxy-4-ethyl-beta-carboline-3-carboxylate, respectively). In the absence of GABA, pentobarbital elicited a maximal current amplitude similar to that of GABA. A minor population of channels is expressed which is open in the absence of GABA or pentobarbital. Mapping subunit gene expression by in situ hybridization histochemistry suggests that the alpha 1-, beta 1-, and gamma 2- subunits are likely receptor constituents in some neuronal populations, e.g., mitral cells of the olfactory bulb, pyramidal cells of the hippocampus, and granule cells of the dentate gyrus and cerebellum.